Elongated Mandibular Premolar: A New Morphological Variant - Heather J. H. Edgar; Paul W. Sciulli (Dental Anthropology Association, 2004)
A previously unreported morphological variant, elongated premolar, is described and analyzed. The elongated premolar is mandibular and may affect the anterior or posterior premolar in the field. It appears phenotypically to be more rectangular (with the long axis mesiodistal) than 'normal' premolars. Dentitions of European Americans, African Americans, and an admixed group of Native African/European Americans were examined for the presence of this characteristic. Elongated premolars were found in 19 teeth in the 458 individuals included in the study. Mesiodistal diameter, buccolingual diameter, and cusp distance were measured for 14 affected and 22 unaffected anterior premolars. Principal components analysis shows that elongated and non-elongated premolars differ primarily in shape and not size, with elongated premolars attaining their overall shape due primarily to an increase in the mesiodistal dimension. Thus, the suggested description of this feature is elongated premolar (referring to the mesiodistal dimension), rather than compressed premolar (referring to the buccolingual dimension).